2014
DOI: 10.1142/s0192415x14500773
|View full text |Cite
|
Sign up to set email alerts
|

Amomum tsao-ko Suppresses Lipopolysaccharide-Induced Inflammatory Responses in RAW264.7 Macrophages via Nrf2-Dependent Heme Oxygenase-1 Expression

Abstract: Amomum tsao-ko Crevost et Lemaire, used as a spice in Asia, is an important source of Chinese cuisine and traditional Chinese medicines. A. tsao-ko is reported to exert a variety of biological and pharmacological activities, including anti-proliferative, anti-oxidative and neuroprotective effects. In this study, NNMBS227, consisting of the ethanol extract of A. tsao-ko, exhibited potent anti-inflammatory activities in RAW264.7 macrophages. We investigated the effect of NNMBS227 in the suppression of pro-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…Furthermore, large amounts of neutrophils, as well as signicantly increased MPO activity can be found in microvessels in lung biopsy tissue sections. 26 This study reported similar ndings, indicating that neutrophils play an important role in the process of inammation caused by endotoxins. This is mainly because activated neutrophils can release large amounts of free radicals and proteases that promote pulmonary edema and microvascular permeability.…”
Section: 28supporting
confidence: 66%
See 3 more Smart Citations
“…Furthermore, large amounts of neutrophils, as well as signicantly increased MPO activity can be found in microvessels in lung biopsy tissue sections. 26 This study reported similar ndings, indicating that neutrophils play an important role in the process of inammation caused by endotoxins. This is mainly because activated neutrophils can release large amounts of free radicals and proteases that promote pulmonary edema and microvascular permeability.…”
Section: 28supporting
confidence: 66%
“…[21][22][23] However, an excessive or continuous inammatory response is closely related to the development of numerous diseases, such as acute lung injury (ALI), asthma, inammatory bowel disease, sepsis, or cancer. [24][25][26] In the process of development of these diseases, the inammatory response plays a critical role. Previous studies have found that at the site of inammation, macrophages release large amounts of proinammatory factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue and cells have a series of defensive mechanisms in response to oxidative stress and injury to alleviate cell injury [38]. Nrf2 is currently considered a key transcription factor that regulates the defense of cells against oxidative injury [39][40][41][42]. Upon exposure to ROS or the indirect effect of phosphorylation, Nrf2 is released from Keap1 and translocated into the nucleus to bind to the ARE sequence, triggering the transcription of downstream phase II antioxidant genes, such as catalase (CAT), NADPH: quinone oxidoreductase (NQO1), superoxide dismutase (SOD), thioredoxin 1 (Trx-1), and heme oxygenase-1 (HO-1), and enhancing the antioxidant capacity of cells [12,13,43,44].…”
Section: Discussionmentioning
confidence: 99%